SOME ASPECTS OF QUALITY OF COOKED FROZEN PRAWNS - Pillai, V Krishna; Lekshmy, A (Indian Journal of Fisheries, 2011)
PRAWNS of more than 100 counts to the pound are generally precooked before freezing and packing. As in the case of all precooked frozen foods expert care is required to maintain high quality in cooked frozen prawns also. A total bacterial count of 100,000-200,000 per gram muscle is suggested as an arbitrary limit for an acceptable quality of cooked frozen prawn in many countries (Goresline, 1959). The freshness of raw material, no doubt, decides to a large extent the quality of the final pack. A raw material of questionable freshness may yield a product having off odours and flavour